Taking production relations seriously: the role of defence firms in armaments cooperation. Issue 4 (2nd October 2018) - Kurc, Caglar; Oktay, Sibel
ABSTRACT: Coordinating defence-industrial relations towards harmonising and facilitating procurement policies, production processes and the joint operability of their member-states' national defence sectors, International Armaments Organisations (IAOs) play an important role in armaments cooperation. How can we explain their institutional development? Existing literature tackles this question using International Relations theories to mid-range theories of institutions and integration. However, they adopt overly state-centric viewpoints, assume actor interests as given, and disregard the changes in the global economic landscape that constitute the backdrop of armaments cooperation. In response, we shift the focus onto a key group of actors: the defence firms. Using a Neo-Gramscian Historical Materialist approach, we investigate how the globalisation of the defence market has created a transnational defence-industrial class in Europe, and demonstrate how its economic interests have fundamentally shaped the institutional frameworks of European IAOs. We focus on the Organisation for Joint Armaments Cooperation (OCCAR) and the European Defence Agency (EDA) to illustrate our argument. Our conclusions have implications for the study of armaments cooperation, particularly highlighting how the economic nature of this policy domain necessitates a closer look at the global and regional production relations, and the agency of the defence firms.